Pendampingan Dan Sosialisasi Model Yang Tepat Pada Ibu Menyusui Di Wilayah Kerja Puskesmas Tamalanrea Kota Makassar - Pratiwi, Cici; Surtikanti, Surtikanti; Artinanda, April; Karnely, Karnely; Darwis, Amelia; Lubis, Halimatussakdiyah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Breastfeeding is a natural activity of giving breast milk to babies or toddlers from the mother's breast. This process is also known as early initiation of breastfeeding where breast milk will only come out after the placenta is released. The purpose of this Community Service Program is to increase the knowledge of breastfeeding mothers in breastfeeding babies. This Community Service Program method is carried out by mentoring and socializing through preparation, implementation and evaluation. Furthermore, pretest and post-test are carried out on all participants. The conclusion of the implementation of this community service activity is that there is an increase in the knowledge and skills of postpartum mothers about the implementation and can apply the right model to breastfeeding mothers properly, especially in the work area of ​​the Tamalanrea Health Center, Makassar City.